2019
DOI: 10.31788/rjc.2019.1245394
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Groundwater Quality in Premonsoon and Post-Monsoon Seasons of a Year Using Water Quality Index (Wqi)

Abstract: Water Quality Index-WQI is useful to transfer complex information of the groundwater quality data into comprehensible and useable data. In this research work, the investigation is carried out by collecting 66 groundwater samples and amalgamating nine water quality parameters for evaluation of groundwater utilizing WQI in pre-as well as post-monsoon of a year in the villages of Gara Mandal of Srikakulam District in Andhra Pradesh. The results confirmed that most of the groundwater sample locations (54.5% of gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…Yadav and Mishra (2014) observed the same minimum or maximum results for groundwater pH, which supports our investigation. The salinity risk and quality of groundwater can be determined with the help of electrical conductivity (Mahalakshmi and Rivachandrabose, 2021;Rao, et al, 2019). During the present study period, ECs were observed in the range of 370-5260 µS/cm (Table 3).…”
Section: Resultsmentioning
confidence: 78%
“…Yadav and Mishra (2014) observed the same minimum or maximum results for groundwater pH, which supports our investigation. The salinity risk and quality of groundwater can be determined with the help of electrical conductivity (Mahalakshmi and Rivachandrabose, 2021;Rao, et al, 2019). During the present study period, ECs were observed in the range of 370-5260 µS/cm (Table 3).…”
Section: Resultsmentioning
confidence: 78%
“…The pH of the samples ranged between 7.9 and 6.11. The pH values in the pre-monsoon were higher in samples from the pre-monsoon of 2022, which might be due to the high temperature in the pre-monsoon (Rao and Krishna, 2019). The standard limits set by WHO and NDWQS for pH are 6.5-8.5.…”
Section: A Hydrogen Ion Concentration (Ph)mentioning
confidence: 90%
“…The average alkalinity of the samples shows that 29.67% of the wells exceed the WHO guidelines. High alkalinity in water can affect the taste of water and cause negative effects on human health, such as metabolic alkalosis (Rao et al, 2019).…”
Section: F Alkalinitymentioning
confidence: 99%
See 2 more Smart Citations